Philological Notes on the Letter lambda in a New Greek-English Dictionary. IV. λογοσκόπος – λωφάω - Olson, S. Douglas (Hyperboreus, 2025)
Part IV. Two generations ago, Robert Renehan published a series of articles expanding, refining, and correcting entries in the 9th edition of the monumental Liddell–Scott–Jones Greek-English Lexicon (1940) as supplemented by Barber and his fellow editors (1968). These notes on the letter lambda in the new Brill Dictionary of Ancient Greek are offered in a similar spirit.